Determination of point of departures based on high throughput in vitro metabolomics - Zickgraf, F. M.; Giri, V. (Spanish Journal of Environmental Mutagenesis and Genomics, 2023)
Metabolomics in vitro poses a high potential for a biologically driven risk assessment approach. We recently developed a platform for high throughput in vitro testing based on LC-MS targeted metabolomics in HepG2 cells. This screening platform was optimized for various parameters such as cell seeding density, passage number, sample preparation, analytical method, etc. and could be used to identify different liver toxicity mode of actions. To determine biologically relevant dose concentrations useful for in vitro to in vivo extrapolation, it is required to determine a point-of-departure (PoD). We present here an approach to determine PoD from a dose response curve determined from multivariate metabolomics data. This approach establishes an important connection for translating results from in vitro systems to in vivo and thus human relevance. Taken together, our metabolomics in vitro system demonstrates applicability for mode of action identification in vitro as well as POD determination